2016
DOI: 10.1146/annurev-astro-081915-023307
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational Instabilities in Circumstellar Disks

Abstract: Star and planet formation are the complex outcomes of gravitational collapse and angular momentum transport mediated by protostellar and protoplanetary disks. In this review we focus on the role of gravitational instability in this process. We begin with a brief overview of the observational evidence for massive disks that might be subject to gravitational instability, and then highlight the diverse ways in which the instability manifests itself in protostellar and protoplanetary disks: the generation of spira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
380
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(408 citation statements)
references
References 205 publications
7
380
1
1
Order By: Relevance
“…These studies have revealed spiral arms in a growing number of disks (Figure 1), both prominent near-symmetric twoarm spirals (e.g., Grady et al 2013;Benisty et al 2015) and more flocculent multiarm spirals on smaller scales and at lower contrast (e.g., Fukagawa et al 2004;Hashimoto et al 2011). Spiral arms can be produced by either gravitational instability (e.g., Rice et al 2003;Lodato & Rice 2004;Stamatellos & Whitworth 2008;Kratter et al 2010;Kratter & Lodato 2016) or the presence of massive companions (gas giant to stellar masses; e.g., Kley & Nelson 2012;Zhu et al 2015;Muñoz & Lai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed spiral arms in a growing number of disks (Figure 1), both prominent near-symmetric twoarm spirals (e.g., Grady et al 2013;Benisty et al 2015) and more flocculent multiarm spirals on smaller scales and at lower contrast (e.g., Fukagawa et al 2004;Hashimoto et al 2011). Spiral arms can be produced by either gravitational instability (e.g., Rice et al 2003;Lodato & Rice 2004;Stamatellos & Whitworth 2008;Kratter et al 2010;Kratter & Lodato 2016) or the presence of massive companions (gas giant to stellar masses; e.g., Kley & Nelson 2012;Zhu et al 2015;Muñoz & Lai 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to our models, the disk, with a mass of about 1.3×10 −3 M , is not massive enough to be gravitationally unstable (Kratter & Lodato 2016). One explanation for such a complex structure is the presence of planet(s) which can interact with the protoplanetary disk and create features (annuli, spirals or vortices) which can be more easily detected than the planets themselves (Kley & Nelson 2012;Baruteau et al 2014).…”
Section: Structure Of the Diskmentioning
confidence: 84%
“…Importantly, in the case of a cavity + a horseshoe, the horseshoe might not be a vortex but might be induced naturally if the arXiv:1712.08845v3 [astro-ph.EP] 12 Feb 2018 disc surrounds a binary system (Ragusa et al 2017). Finally, spirals might also be produced by the development of gravitational instabilities (Kratter & Lodato 2016), by an external high-mass perturber undergoing a flyby (Quillen et al 2005) or induced dynamically as a consequence of a different irradiation from the star due to a warp in the inner disc (Montesinos et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Discs with Q < 2 are subject to gravitational instabilities that generate effective α > 0.01 or ν > 10 −4 r 2 p p (Kratter & Lodato 2016). Even for a factor of ∼5-10 decrease in F crit (increase in Q), disc self-gravity may suppress large-scale vortex formation via the RWI (Lin & Papaloizou 2011).…”
Section: Constraints From Planet Formation Modelsmentioning
confidence: 99%